Współczesne filozoficzne interpretacje psychoanalizy Sigmunda Freuda. Przegląd wybranych stanowisk - Szmaglińska, Katarzyna (Folia Philosophica, 2018)
The author of the paper discusses three of contemporary interpretations ofFreud’s psychoanalysis. Most recent interpretations go beyond one-sidedness of pre-vious ones (that is, biologism and hermeneutics) which took theory and practice sep-arately. Thanks to reconstruction of some of philosophical consequences of Freud’sthought — ontological (anthropological), epistemological and ethical — psychoanaly-sis might be taken as metaphysical concept (Andrzej Leder), moral philosophy(Alfred I. Tauber) or it might be interpreted dialectically (Jon Mills). The authorpoints out some key elements of Freud’s theory, which make these interpretationspossible, and in this way she highlights validity of Freud and vivid reception of histhought in philosophy.